2021
DOI: 10.1183/13993003.03468-2020
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes in sarcoidosis are potent tumour necrosis factor producers and predict disease outcome

Abstract: BackgroundPulmonary sarcoidosis is an inflammatory disease characterised by granuloma formation and heterogeneous clinical outcome. TNF is a proinflammatory cytokine contributing to granuloma formation and high levels of TNF have been shown to associate with progressive disease. Mononuclear phagocytes (MNPs) are potent producers of TNF and highly responsive to inflammation. In sarcoidosis, alveolar macrophages (AMs) have been well studied. However, MNPs also include monocytes/monocyte-derived cells and dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…In addition, previous studies reported that immune cells constituting recurrent sarcoidosis granulomas in lung transplant allografts originated from the recipient monocyte-macrophage lineage ( 19 , 20 ). Finally, the inflammatory phenotype of MD-macrophages in pulmonary sarcoidosis and their propensity to produce TNFα has been recently highlighted ( 11 ), supporting the role of these cells in sarcoidosis pathogenesis. However, the fact that experiments were almost exclusively performed in MD-macrophages constitutes a limitation of the present study.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, previous studies reported that immune cells constituting recurrent sarcoidosis granulomas in lung transplant allografts originated from the recipient monocyte-macrophage lineage ( 19 , 20 ). Finally, the inflammatory phenotype of MD-macrophages in pulmonary sarcoidosis and their propensity to produce TNFα has been recently highlighted ( 11 ), supporting the role of these cells in sarcoidosis pathogenesis. However, the fact that experiments were almost exclusively performed in MD-macrophages constitutes a limitation of the present study.…”
Section: Discussionmentioning
confidence: 92%
“…The subset distribution differed mostly based on the sampling site as described before. 9,17,20 Analyzing the transcriptome of blood and BAL cells from sarcoidosis patients has often been performed on bulk cells, thereby masking the gene expression by less frequent immune cell subsets. 20,34 Using RNA sequencing, we showed significant differences in genes expression between DCs, monocytes, and monocyte-derived cells from blood and BAL of sarcoidosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…1D), as previously reported. 9,20 Next, DCs, monocytes, and monocyte-derived cells were FACS-sorted and postsorting purity of cells was confirmed to be >95% for each patient and exemplified for 1 patient with May-Grünwald-Giemsa staining (Fig. 1E).…”
Section: Dcs From Sarcoidosis Patients Display a Gene Expression Profile Suggestive Of Superior Antigen Presentation And T Cell Activatiomentioning
confidence: 92%
See 2 more Smart Citations